Effects of regulation on interaction pattern in web-based collaborative writing activity. Issue 1 (27th January 2022) - Wang, Linnan
Abstract: Although regulation has become a critical method to improve the effect of collaborative writing in L2 classes, it is still not clear how the regulation activities influence peer interactions, which is important for improvement of regulation itself. This case study examined dynamic interactions of several small teams of ESL students when they performed two collaborative argument writing tasks without and with regulation. Interaction patterns were identified in terms of 'equality' and 'mutuality' and different interaction patterns occurred when these learners switched between tasks. The dynamic features of peer interactions were explained according to an extended activity model. This study enriched the observation of how regulation affected peer interactions through sociocultural factors. The result can provide insights into how regulation activity should be designed and improved for web-based collaborative writing activities in L2 classes.